Plan de mejoramiento del clima laboral y cultura organizacional de la empresa pasteurizadora Tanilact de la ciudad de Latacunga provincia de Cotopaxi año 2023 - Chiluisa Imbaquingo, Pamela Lizbeth (2023)
The present investigation was developed in the Pasteurizing dairy company "TANILACT", with the objective of carrying out an improvement plan in the work environment and organizational culture, variables that will be investigated in the development of the work, for which the analysis between the workers of the company dedicated to the production and commercialization of dairy products of exquisite flavors and quality. The company that is evaluated is considered medium for its daily production, it is in permanent search of progress in its objectives and goals, particularly that due to multiple factors have not been possible to achieve. In relation to the methodology, it is a descriptive, analytical investigation, which allowed measuring the variables of the work environment and organizational culture through the instruments based on the actors Marvin Weisbord and Daniel Denison 2023.